APLIKASI PENGENALAN OBJEK WISATA SEJARAH KOTA TUA JAKARTA BERBASIS AUGMENTED REALITY - Agung Selamet Riadi; anton anton; Ummu Radiyah (Jurnal Teknika, 2018)
The world of tourism in Indonesia, especially  DKI Jakarta, has developed rapidly. One of the tourism object in Jakarta is  Old Town  tour  (Kota Tua). About thirty percent of visitors who came to the Kota Tua area,  generally come  only  to  take  pictures,  bike  or  just  gather.  To  provide  a  unique  experience  and  historical  knowledge  to tourists, an application of  augmented  reality is made that can be used by tourists when visiting Jakarta's  Kota Tua area. In the application created there are three-dimensional objects, photos, as well as general informationsand historical informations  of attractions in the  Kota Tua  Jakarta.  The method of this  research  using  waterfall model  as  a  system  development  model  with  five  stages  namely  Requirement  Analysis,  System  Design, Implementation, Integration and Testing, Operation and Maintenance.